2013
DOI: 10.1097/prs.0b013e31828e2159
|View full text |Cite
|
Sign up to set email alerts
|

Free Tissue Transfer in the Obese Patient

Abstract: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Numerous studies have confirmed that obese patients experience increased surgical complications, specifically wound healing complications. 3,4,11,14,17,[22][23][24][25] Wound healing complications in obesity have been linked to decreased myofibroblast activity and disrupted collagen maturation. 26,27 Fischer et al concluded that wound healing complications in obese patients are likely related to increased tissue tension, attenuated wound healing capacity, and extensive dissections required for flap harvest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed that obese patients experience increased surgical complications, specifically wound healing complications. 3,4,11,14,17,[22][23][24][25] Wound healing complications in obesity have been linked to decreased myofibroblast activity and disrupted collagen maturation. 26,27 Fischer et al concluded that wound healing complications in obese patients are likely related to increased tissue tension, attenuated wound healing capacity, and extensive dissections required for flap harvest.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Fischer et al concluded that wound healing complications in obese patients are likely related to increased tissue tension, attenuated wound healing capacity, and extensive dissections required for flap harvest. 23 A multivariate regression model was created to control for confounding factors and to assess whether obesity carries an intrinsic risk for any postoperative complication following free flaps. The most significant odds for any complication were in class II (OR: 1.23; p ¼ 0.004) and III obesity (OR: 1.45, p < 0.001) groups.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical group will be further subdivided into intraoperative and post-operative. Complications will be strati ed according to the Clavien-Dindo classi cation (30)(31)(32). Finally, if available any assessment of pre-operative tness will be recorded.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The surgical group will be further subdivided into intraoperative and post-operative. Complications will be stratified according to the Clavien-Dindo classification [35][36][37]. Finally, if available any assessment of preoperative fitness will be recorded.…”
Section: Secondary Outcomesmentioning
confidence: 99%